Which women (don’t) leave and which men (don’t) stay? Gender and the diversity of forms and the temporality of contemporary intimate relationships - Emilia Paprzycka; Edyta Mianowska (Acta Universitatis Lodziensis: Folia Sociologica, 2020)
The article focuses on relationship experiences in the light of the diversity of relationship forms, relationship length and the attitude of partners to relationship permanence. The conceptual framework was determined by the sociotemporal perspective, and the analysis was carried out with reference to concepts employed in the fields of the sociology of the family, the sociology of intimacy, the sociology of gender and the sociology of time. The aim of the study was to determine the relationship between the socio-demographic characteristics of women and men and their relationship experiences, the diversity of relationship forms and their length, as well as their readiness to stay in a relationship or leave in a crisis situation. The research was carried out using the diagnostic survey method on a representative sample of adult Poles in January 2018. Gender has been shown to differentiate the length of relationship and the attitudes to relationship permanence. It was found that women stay in shorter relationships more often than men. It was also found that the experiences of women with different types of relationships are more diverse when linked to their social status than the experiences of men. Four types of orientation to the (im)permanence of relationships were identified. It was established that men’s readiness to leave depends on their age, education and self-assessment of their financial situation, whereas women’s decision to leave depends on their age, education and socio-occupational category.